PENERAPAN MODEL PEMBELAJARAN TPS (THINK, PAIR AND SAHRE) UNTUK MENINGKATKAN KETERAMPILAN MEMBACA SISWA KELAS X IPA 4 SMAN 1 PRINGGARATA - JUPRI JUPRI (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2023)
This study concerns with Think Pair Share (TPS) to improve students’ reading skill. The aim of this study was to promote students’ reading skill through (TPS) technique . In this study, the researcher applied classroom action research in which the datas were described in qualitative and quantitative description using the instruments of observations such as checklist, test and documentation .Observation was conducted to know the implementation of (TPS) technique during teaching and learning process and its datas were decribed in qualitative description, while a writeen test is used to measure the students’ achievement in reading skill then the results are described in quatitative description. Subject of this study was tenth- grade of SMAN 1 Pringgarata which consists of 33 students.This study was conducted in two cycles, each cycle consisted of 4 steps such as: planning, acting, observing and reflecting. The result of this research showed that (TPS) technique could promote students’ reading skill. It could be seen from the significant improvement of result in each cycle. The average of students’ score before implementing the strategy was 65,83, and increased into 67,88 in the first cycle . After doing treatment and The result increased into 81,67 in second cycle. This means, students’ reading skill was successfully improved by applying (TPS) technique in teaching Reading at the tenth-grade of senior high school, SMAN 1 Pringgarata. ABSTRAKPenelitian ini bertujuan untuk mendeskripsikan perencanaan, pelaksanaan dan evaluasi peningkatan pembelajaran keterampilan membaca pada siswa kelas X IPA 4 SMA Negeri 1 Pringgarata dengan menggunakan metode TPS (Think Pair Share). Penelitian ini merupakan penelitian tindakan kelas (PTK) dan datanya dipaparkan melalui data deskripsi kualitatif dan kuantitatif. Penelitian ini dilaksanakan dalam dua siklus. Setiap siklus terdiri dari atas 4 tahap yaitu: tahap perencanaan, pelakasanaan, tindakan, observasi dan refleksi. Data proses pembelajaran, setiap siklus dianalisis secara deskriptif kualitatif. Sedangkan data hasil pembelajaran dianalisis secara deskriptif kuantitatif. Subjek penelitian ini adalah siswa kelas X IPA 4 yang berjumlah 33 orang. Hasil penelitian menunjukkan bahwa nilai rata-rata yang diperoleh siswa pada siklus I adalah 67,88 % dengan ketuntasan klasikal sebesar 30,3% sedangkan pada siklus II nilai rata-rata mencapai 81,67 dengan ketuntasan klasikal 96,97%. Hasil penelitian menunjukkan bahwa pembelajaran dengan metode TPS dapat meningkatkan keterampilan membaca khususnya teks recount sejarah siswa kelas X IPA 4 SMA Negeri 1 Pringgarata.